Spin selection in single-frequency two-photon excitation of alkali-metal atoms - Krishnapriya Subramonian Rajasree; Ratnesh Kumar Gupta; Vandna Gokhroo; Fam Le Kien; Thomas Nieddu; Tridib Ray; Síle Nic Chormaic; Georgiy Tkachenko (Physical Review Research, 2020)
We develop a theoretical framework for spin selection in single-frequency two-photon excitation of alkali-metal atoms as a function of polarization of the excitation light. We verify the theory by experimentally probing the 5S_{1/2}→6S_{1/2} transition rate in ^{87}Rb in two configurations: paraxial light excitation of warm vapor and nonparaxial excitation of laser-cooled atoms. The transition rate follows a quadratic dependence on the helicity parameter linked to the excitation light's polarization. For paraxial excitation, the transition rate scales as the squared degree of linear polarization, being zero for circularly polarized light. In contrast, for nonparaxial excitation via an optical nanofiber, the two-photon transition is not completely extinguished by varying the light polarization. Our findings lead to a deeper and more universal understanding of the physics of multiphoton processes in atoms.